Electro-acupuncture (EA) as an adjunct therapy to methadone maintenance treatment (MMT) in heroin addiction: a study of 2D EEG power spectral topography and Morlet wavelet - Shiman, F.; Molaei, F.; Oladazimi, M.; Abd Rashid, R.; Habil, H.; Ibrahim, F. (2012)
The present study investigates the efficiency of electro acupuncture (EA) as an adjunct therapy to methadone maintenance treatment (MMT) in heroin dependents. Time-frequency analysis, based on Morlet wavelet transform together with 2D spectral power topography were applied to demonstrate different brain dynamics in subjects being acupunctured as compared to controls. A significant decrease of delta activity in right hemisphere together with an increase of alpha activity in central areas was observed in subjects who underwent acupuncture which may indicate the modulatory effects of electro-acupuncture as a treatment to improve the conditions of opioid dependency. Â© 2012 IEEE.